2008
DOI: 10.1530/eje-07-0484
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic–pituitary insufficiency following infectious diseases of the central nervous system

Abstract: Objective: Hypothalamic-pituitary insufficiency may have diverse causes. The aim of this study was to determine the incidence of hypothalamic-pituitary insufficiency in patients with previous infectious diseases of the central nervous system (CNS) of different etiologies and mild-to-moderate clinical course. Design: Patient series. Basal and stimulated (insulin tolerance test) pituitary function testing was performed in 19 patients with previous neuroborreliosis, encephalitis, or meningitis following an interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…These deficiencies may be either transient or permanent, and may occur immediately or few months later. The frequency of this long term anterior pituitary dysfunction after acute meningitis may be more common than hitherto reported (Lam et al, 1993;Tanriverdi et al, 2008;Schaefer et al, 2008;Tsiakalos et al, 2010;Tuazon and Migulues, 2001). These data suggest that decreased linear growth may be explained by decreased growth hormone (GH) secretions and consequently insulin-like growth factor-I (IGF-I) production.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…These deficiencies may be either transient or permanent, and may occur immediately or few months later. The frequency of this long term anterior pituitary dysfunction after acute meningitis may be more common than hitherto reported (Lam et al, 1993;Tanriverdi et al, 2008;Schaefer et al, 2008;Tsiakalos et al, 2010;Tuazon and Migulues, 2001). These data suggest that decreased linear growth may be explained by decreased growth hormone (GH) secretions and consequently insulin-like growth factor-I (IGF-I) production.…”
Section: Discussionmentioning
confidence: 68%
“…Growth hormone (GH) and gonadotropin deficiencies were the most common abnormalities observed. In two retrospective studies published in 2008, partial hypopituitarism after CNS infections was found in 20 and 28% of patients, respectively (Tanriverdi et al, 2008;Schaefer et al, 2008). Isolated severe GH deficit was found in the second study (Schaefer et al, 2008).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Hypopituitarism (failure of the pituitary gland) is a clinical syndrome that develops as a result of insufficient production and release of one or more of the pituitary hormones. Pituitary insufficiency may have diverse causes, the most common being pituitary adenoma, craniopharyngioma, Sheehan's syndrome, lymphocytic hypophysitis, infiltrative diseases, irradiation, and traumatic brain injury or surgery [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculous meningitis, which is a common cause of bacterial meningitis, has long been known to cause pituitary dysfunction (3). Among the various causes of pituitary insufficiency, infectious diseases of the central nervous system (CNS) are relatively rare, and have primarily been reported in only three retrospective and two prospective studies [1,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%